PEMBERDAYAAN PENGURUS BUMDES MELALUI PELATIHAN KETERAMPILAN MANAJERIAL UNTUK MENINGKATKAN EFEKTIVITAS PENGELOLAAN DESA - Wahyuni, Daru; Mustofa, Mustofa; Ngadiyono, Ngadiyono; Wardani, Nita Kusuma; Puspitaningrum, Yuliastuti (Universitas Esa Unggul, 2025)
AbstractThis Community Service (PkM) activity aims to improve the managerial capacity of the Bergas Village-Owned Enterprise (BUMDes) management in Klaten Regency, enabling them to manage the organization professionally, effectively, and sustainably. This program was motivated by the problems of low managerial skills, suboptimal financial management, and minimal use of digital technology in BUMDes operational activities. The implementation method included an initial survey, problem formulation with partners, three days of intensive training, and six months of follow-up mentoring. The training materials focused on three main aspects: preparing digital financial reports, developing human resource soft skills, and digital marketing strategies. The results of the activity showed a significant increase in the participants' ability to prepare application-based financial reports, communicate effectively within the organization, and utilize social media to promote village products. The activity evaluation also showed that 83% of participants understood the material very well, and 75% stated that the training materials were very useful. This program succeeded in improving the professionalism of BUMDes management, strengthening accountability and transparency in financial management, and expanding the digital-based marketing network. Thus, this activity significantly contributes to supporting the achievement of the Sustainable Development Goals (SDGs), particularly in reducing inequality and improving the welfare of rural communities through local economic empowerment. Kata kunci: Community empowerment, Village-Owned Enterprises (BUMDes), managerial skills. AbstrakKegiatan Pengabdian kepada Masyarakat (PkM) ini bertujuan untuk meningkatkan kapasitas manajerial pengurus Badan Usaha Milik Desa (BUMDes) Bergas, Kabupaten Klaten, agar mampu mengelola organisasi secara profesional, efektif, dan berkelanjutan. Program ini dilatarbelakangi oleh permasalahan rendahnya kemampuan manajerial, kurang optimalnya pengelolaan keuangan, dan minimnya pemanfaatan teknologi digital dalam kegiatan operasional BUMDes. Metode pelaksanaan meliputi survei awal, perumusan masalah bersama mitra, pelatihan intensif selama tiga hari, serta pendampingan lanjutan selama enam bulan. Materi pelatihan difokuskan pada tiga aspek utama, yaitu penyusunan laporan keuangan digital, pengembangan soft skill sumber daya manusia, dan strategi pemasaran digital. Hasil kegiatan menunjukkan peningkatan signifikan dalam kemampuan peserta menyusun laporan keuangan berbasis aplikasi, berkomunikasi secara efektif dalam organisasi, serta memanfaatkan media sosial untuk promosi produk desa. Evaluasi kegiatan juga menunjukkan bahwa 83% peserta memahami materi dengan sangat baik, dan 75% menyatakan bahwa materi pelatihan sangat bermanfaat. Program ini berhasil meningkatkan profesionalisme pengurus BUMDes, memperkuat akuntabilitas dan transparansi pengelolaan keuangan, serta memperluas jaringan pemasaran berbasis digital. Dengan demikian, kegiatan ini berkontribusi nyata dalam mendukung pencapaian tujuan pembangunan berkelanjutan (SDGs), khususnya pada aspek pengurangan kesenjangan dan peningkatan kesejahteraan masyarakat desa melalui pemberdayaan ekonomi lokal. Kata kunci: Pemberdayaan masyarakat, BUMDes, keterampilan manajerial.